Lysosomal and network alterations in human mucopolysaccharidosis type VII iPSC-derived neurons. Issue 1 (December 2018) - Bayó-Puxan, Neus; Terrasso, Ana; Creyssels, Sophie; Simão, Daniel; Begon-Pescia, Christina; Lavigne, Marina; Salinas, Sara; Bernex, Florence; Bosch, Assumpció; Kalatzis, Vasiliki; Levade, Thierry; Cuervo, Ana; et al.
Abstract Mucopolysaccharidosis type VII (MPS VII) is a lysosomal storage disease caused by deficient β-glucuronidase (β-gluc) activity. Significantly reduced β-gluc activity leads to accumulation of glycosaminoglycans (GAGs) in many tissues, including the brain. Numerous combinations of mutations inGUSB (the gene that codes for β-gluc) cause a range of neurological features that make disease prognosis and treatment challenging. Currently, there is little understanding of the molecular basis for MPS VII brain anomalies. To identify a neuronal phenotype that could be used to complement genetic analyses, we generated two iPSC clones derived from skin fibroblasts of an MPS VII patient. We found that MPS VII neurons exhibited reduced β-gluc activity and showed previously established disease-associated phenotypes, including GAGs accumulation, expanded endocytic compartments, accumulation of lipofuscin granules, more autophagosomes, and altered lysosome function. Addition of recombinant β-gluc to MPS VII neurons, which mimics enzyme replacement therapy, restored disease-associated phenotypes to levels similar to the healthy control. MPS VII neural cells cultured as 3D neurospheroids showed upregulatedGFAP gene expression, which was associated with astrocyte reactivity, and downregulation of GABAergic neuron markers. Spontaneous calcium imaging analysis of MPS VII neurospheroids showed reduced neuronal activity and altered network connectivity in patient-derived neurospheroids compared to a healthy control. These results demonstrate the interplay between reduced β-gluc activity, GAG accumulation and alterations in neuronal activity, and provide a human experimental model for elucidating the bases of MPS VII-associated cognitive defects.